Hypoxia rescues early mortality conferred by superoxide dismutase deficiency. - Wicks, S.; Bain, N.; Duttaroy, A.; Hilliker, A.J.; Phillips, J.P. (Free Radical Biology and Medicine, 2009)
Oxidative stress is widely associated with disease and aging but the underlying mechanisms are incompletely understood. Here we show that the premature mortality of Drosophila deficient in superoxide scavengers, superoxide dismutase (SOD) 1 or SOD2, is rescued by chronic hypoxia. Strikingly, switching moribund SOD2-deficient adults from normoxia into hypoxia abruptly arrests their impending premature mortality and endows the survivors with a near-normal life span. This finding challenges the notion that irreversible oxidative damage initiated by unscavenged superoxide in the mitochondrial matrix underpins the premature mortality of SOD2-deficient adults. In contrast, switching moribund SOD1-deficient flies from normoxia into hypoxia fails to alter their mortality trajectory, suggesting that the deleterious effects of unscavenged superoxide in the cytoplasm/intermembrane space compartment are cumulative and largely irreversible. We conclude that cellular responses to superoxide-initiated oxidative stress are mediated through different compartment-specific pathways. Elucidating these pathways should provide novel insights into how aerobic cells manage oxidative stress in health, aging, and disease.